2012
DOI: 10.1021/jp307202t
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of Small 4d Transition Metal Clusters: Role of Spin–Orbit Coupling

Abstract: The spin and orbital magnetic moments, as well as the magnetic anisotropy energy (MAE), of small 4d transition metal (TM) clusters are systematically studied by using the spin-orbit coupling (SOC) implementation of the density-functional theory (DFT). The effects of spin-orbit interactions on geometrical structures and spin moments are too weak to alternate relative stabilities of different low-lying isomers. Remarkable orbital contributions to cluster magnetic moments are identified in Ru, Rh, and Pd clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 74 publications
0
27
0
Order By: Relevance
“…Rhodium stands out because it is located at the center of the periodic table with an unfilled 4d shell, which produces rich physical and chemical properties. Rhodium clusters have been intensively studied by using theoretical methods [1][2][3][4][5][6] to understand their catalytic properties and the emergence of the electronic and magnetic properties [7][8][9][10]. Small rhodium clusters were found to possess magnetic moments [11,12] on the order of one Bohr magneton (1μ B ) per atom, making this the only 4d element with magnetic order at the nanoscale and with Mn [13] the only known elements that are magnetic at nanoscale but not in the bulk.…”
mentioning
confidence: 99%
“…Rhodium stands out because it is located at the center of the periodic table with an unfilled 4d shell, which produces rich physical and chemical properties. Rhodium clusters have been intensively studied by using theoretical methods [1][2][3][4][5][6] to understand their catalytic properties and the emergence of the electronic and magnetic properties [7][8][9][10]. Small rhodium clusters were found to possess magnetic moments [11,12] on the order of one Bohr magneton (1μ B ) per atom, making this the only 4d element with magnetic order at the nanoscale and with Mn [13] the only known elements that are magnetic at nanoscale but not in the bulk.…”
mentioning
confidence: 99%
“…In addition, the bonding preference of different atoms gives another efficient way to construct good candidates for the global minima or to reduce the configuration space. In our previous works, this method has been used to treat transition metal (TM) clusters [45][46][47][48][49][50][51] and lanthanide clusters, 18,20,28 for which the lowest energy structures we obtained were positively confirmed by the subsequent works using the unbiased global optimizations. 13,[52][53][54][55][56][57] Following above approaches, we consider all possible configurations for small sizes (n = 2-7), but construct a large number of initial configurations for large sizes (n = [8][9][10][11][12][13][14] primarily at the additive and substitutive patterns from the low-lying structures of Tb n±1 , e.g., three different binding modes are intensively examined for the adsorption of oxygen atom: atop, bridge, and hollow sites.…”
Section: Computational Proceduresmentioning
confidence: 70%
“…As SOC is included, the SOC couples the magnetization to the lattice and determines the direction of magnetization, and both spin and orbital moments will be anisotropic. Previously, Guirado-López's work on Ni clusters 77 as well as our recent works on Pt clusters, 78 Fe clusters, 49 and 4d clusters 51 have demonstrated that the anisotropy of the local moments depends strongly on the local environment. Since anisotropic moment changes sign as a function of atom sites, the cancellation of contributions from different atomic sites often results in a relatively small anisotropy of the average per atom.…”
Section: Effects Of Magnetic Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…4,5 Not only does this enhancement of the magnetic moment occur for the 3d materials that are ferromagnetic in the bulk (Fe, Co, Ni). Also there has been a certain amount of theoretical work for CoRh, some of which included spin-orbit coupling (SOC) 10,11,[13][14][15] but most without. This is true for example in 4d rhodium clusters.…”
Section: Introductionmentioning
confidence: 99%